PENGARUH KREDIBILITAS CELEBRITY ENDORSER DAN DAYA TARIK IKLAN TERHADAP KEPUTUSAN PEMBELIAN INDOMIE - Aris Kurniawan (Institut Teknologi dan Bisnis Dewantara, 2021)
The purpose of this study was to determine and analyze the effect of celebrity endorser credibility variables and advertising attractiveness on Indomie purchasing decisions, questionnaires were distributed to 100 respondents using purposive sampling technique, the data collected were processed by multiple regression method with SPSS version 23. The results showed that credibility Celebrity Endorser has a positive and significant effect on Indomie Purchase Decisions, Ad Attractiveness has a positive and significant impact on Indomie Purchase Decisions, Celebrity Endorser Credibility and Advertising Attractiveness simultaneously have a positive and significant effect on Indomie Purchase Decisions.